(untitled) (Quinto Sol, 2014)
This article intends to carry out a social profile of a group of “black” and “mulatto” petitioners of Buenos Aires who appealed to the “Real Audiencia” -and then “Corte de Apelaciones”- to be declared “solemn poor” in order to litigate without cost in different courts. In this way, we will approach the different ways of integration of the African-descendent population of the capital of Viceroyalty during the period 1786-1821. We will look into the problems of their everyday lives, in specific hardships of their socioethnic condition and the success they had going to court in search of this benefit. This will allow us to know how social stratification variables such as gender, race, or class, interacted in a dynamic and specific context as it was the city of Buenos Aires between the end of the colonial era and the first revolutionary decade.